Collins Spanish-English English-Spanish dictionary - Smith, Colin (Collins LondonGB, 1984)
Contains over 160,000 current words and phrases. Includes alternative spellings, parts of irregular verbs, contracted forms, prefixes and suffixes and parts of compound words.